Meningkatkan Motivasi Belajar Siswa dengan Permainan 'Jelajahi Sekolahku' dalam Pembelajaran Pendidikan Pancasila - Rahmah Maulidi, Saniyatul Mafarrikhah; Pangestu, Widya Trio (Jurnal Kewarganegaraan, 2025)
The lack or decline of students' learning motivation requires highly engaging learning activities, one of which is by implementing learning innovations through games that can be used as learning media. This study aims to determine the effect of the "Explore My School" game on increasing students' learning motivation. This research employs a quantitative experimental method with a one-shot case study design to test the predetermined hypothesis, conducted in Grade IV of SDN Sidotopo Wetan I/255 Surabaya. The implementation of the "Explore My School" game received positive responses from students, as they perceived the activity as making their classroom atmosphere more engaging. Observations also indicated that students appeared highly enthusiastic when the game was introduced. The conclusion of this study suggests that the game successfully increased students' learning motivation, as shown by their improved learning outcomes. This is evidenced by the hypothesis test results, where the t-value was 2.846, which is greater than the t-table value, leading to the acceptance of the alternative hypothesis (Ha). Additionally, this study can serve as a reference for teachers regarding one of the effective ways to enhance students' learning motivation.